2014
DOI: 10.18677/agrarian_academy_2014_019
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasia E Procedimentos Anti-Hemorrágicos

Abstract: RESUMOA hemostasia é um processo fisiológico complexo que resulta no fim da hemorragia no local de injúria de um vaso. O dano vascular desencadeia o inicio da formação do coágulo com o objetivo de produzir um tampão de fibrina e plaquetas, para prevenir a perda sanguínea. Ao considerar as ferramentas que os cirurgiões dispõem para combater as hemorragias, é importante enfatizar a necessidade de um conhecimento profundo da anatomia e experiência cirúrgica. Historicamente, as suturas têm sido a principal forma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the cupuaçu seed, five secondary metabolites that have few studies in the scientific literature were identified: After analyzing the results of biological activities (Table 1), the molecules appear to be promising as hemostatic (isoscutelarein A, theograndin I, theograndin II, hypolaetin A and hypolaetin B). These results demonstrate great biological importance, since hemostatic action can control and stop bleeding, being clinically relevant in situations of surgery, trauma, and people with hemolytic disorders (Prado et al, 2014).…”
Section: Prediction Of Biological Activitiesmentioning
confidence: 80%
“…In the cupuaçu seed, five secondary metabolites that have few studies in the scientific literature were identified: After analyzing the results of biological activities (Table 1), the molecules appear to be promising as hemostatic (isoscutelarein A, theograndin I, theograndin II, hypolaetin A and hypolaetin B). These results demonstrate great biological importance, since hemostatic action can control and stop bleeding, being clinically relevant in situations of surgery, trauma, and people with hemolytic disorders (Prado et al, 2014).…”
Section: Prediction Of Biological Activitiesmentioning
confidence: 80%